How Does Employee Performance Increase Tourist Visits? : Empirical Confirmation in the Covid-19 Moment - Erwin Kurniawan A.; Sri Langgeng Ratnasari; Herni Widiyah Nasrul (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2022)
It is difficult to demand employee productivity, especially when Covid-19 limits social interaction. Continuous extra attention needed so that employee performance gets optimal evidence. By focusing on leadership styles, organizational commitment, and job satisfaction, this study attempts to select how these three factors transmit the performance of ‘Resort X’ employees in the Anambas (Province of Riau Islands, Indonesia). The sample involves the entire population to be asked for information related to relevant questions about these variables through census techniques. After the questionnaires distributed and collected, data validation applied using multiple linear regression methods and IBM SPSS. Effects simultaneously and partially describe that leadership style, organizational commitment, and job satisfaction play a significant role in employee performance. Despite the disruption caused by the global pandemic, it did not change the productivity of employees in promoting and attracting tourist visits. Tourist destinations need to adapt and strive for recovery through optimal resources.